1999
DOI: 10.1093/humrep/14.3.698
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine insemination treatment in subfertility: an analysis of factors affecting outcome

Abstract: A total of 811 intrauterine insemination (IUI) cycles in which clomiphene citrate/human menopausal gonadotrophin (HMG) was used for ovarian stimulation were analysed retrospectively to identify prognostic factors regarding treatment outcome. The overall pregnancy rate was 12.6% per cycle, the multiple pregnancy rate 13.7%, and the miscarriage rate 23.5%. Logistic regression analysis revealed five predictive variables as regards pregnancy: number of the treatment cycle (P = 0.009), duration of infertility (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
153
11
27

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(222 citation statements)
references
References 48 publications
22
153
11
27
Order By: Relevance
“…ongoing pregnancy instead of delivery. In this age group delivery rates per cycles were reported in several papers [2,9,11,18,24] and varied from 1.4 % up to 9.8 % per cycle. In our study 63 IUI patients achieved a low crude cumulative delivery rate of 7.8 %.…”
Section: Discussionmentioning
confidence: 88%
“…ongoing pregnancy instead of delivery. In this age group delivery rates per cycles were reported in several papers [2,9,11,18,24] and varied from 1.4 % up to 9.8 % per cycle. In our study 63 IUI patients achieved a low crude cumulative delivery rate of 7.8 %.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, we also observed that as the infertility duration became longer, the gestation rates also increased. However, in the literature, many studies have indicated that as the age (5,8,17) and infertility duration (7,17,18) increase, gestational rates decrease. Also, Ibérico et al (19) reported in a study published in 2004 that gestational rates in IUI decreased independently of the age through longer infertility durations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there are many studies related to age (4), the ovarian reserve of females (5) and sperm parameters in males (6), and the duration and type of infertility (7), which are pre-cycle parameters. Furthermore, the effects of cyclic parameters, such as selected ovulation induction protocols and the characteristics of the obtained follicles, have been evaluated on IUI outcomes in different studies (8)(9)(10). Despite all these studies, there is still no consensus on parameters that can predict the chances of clinical pregnancy after IUI.…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine insemination is most frequently used (15). Although this is a low risk procedure, it is expensive, requiring sperm preparation in the laboratory and usually controlled ovarian stimulation and ultrasonography, generally restricting the treatment to specialized centers (16).…”
mentioning
confidence: 99%